Diversidade e identidade religiosa: Uma leitura espacial dos padroeiros e seus festejos em Múquem, Abadiânia e Trindade-GO - D'ABADIA, Maria Idelma Vieira (2011)
The religious feasts, in a general set, are related to the celebrations and tributes done to the worshiped deities in any other religious follow-up. The present study emphasizes the religious feasts as a social cultural practice that spatializes in Goiás State. The feasts space materializes itself in the scenery, in the territory and in the territorialities construction. The chosen places to the research development are the villages of Muquém and Posse D Abadia, respectively set in the goiano boroughs of Niquelândia and Abadiânia and the town of Trindade. The catholic religious feasts are manifestations that boost these boroughs spaces, revealing, in their organization, a religious identity expressed in the studied places territory. The work main goal is the comprehension of how it occurs the patron feasts spatialization and its reflexes in the formation and structuration of the goiano territorial and cultural space. With this study it is searched to present a theoretical-methodological reflection about the patron feasts traditions that sustain a territorial identity in the State. For this identity, the patron is the faith, territory and the feast centrality. The territory is built and donated to the patron, which domain is effective with the possession and the power as protector of the mentioned places. The territorial identity is placed as a religious identity assigned to this patron. The formed identity, in first place, is the religious icon represented in the image of N. S. da Abadia and in the medallion of Divino Pai Eterno. The historical foundations that explain the process of emergence and formation of the three places enable to discuss that the miracle in Muquém, the meeting of the image in Trindade and the spontaneous institution of the prayers in Posse are elements responsible for the emergence of the patrons connected to the territory. The scientific contribution to the methodological development of the research is guided by the cultural approach of geography, formed, nowadays, by studies that postulate a methodological path mixed by the intersection among several elements that compose a culture, in which the interpretation, comprehension and intentionality of the lived space are essential. In this way, this approach establishes the recognition possibility of the daily acts that involve life, frequently neglected, by an apprehension pathway that unveils such as this momentary as the own symbolic lived world. The cultural geography contributes for the patron feast study by allowing the conceptual (re) elaboration of its particularities, from the symbolic representation systems, methodological way of communication that allows to chain the feeling and the stories of life of the human groups to the resignificance and organization of the space process and of its cultural practices. By this way, in what concerns the territorial identitary dimension that permeates the popular feasts and devotionals to the Goiás State, the patron feast posses the primordial element of identitary territory articulation, being on the rural zone or the country and metropolitan towns, in the evocation and respect to the patron saints, keeping the tradition alive.